Penerapan Komunikasi Profetik dalam Dakwah Inklusif di Pesantren Waria Al-Fattah Yogyakarta - Maria Al-Zahra Ning Widhi; Isnaini Masruroh; Kholid Achmad (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
Indonesia's Constitution guarantees freedom of religion and worship. However, transgender community often experience discrimination, one of which is in terms of worship. Waria who are Muslims also have the right to worship and learn their religion. This study aims to explain the method of inclusive da'wah in the Pesantren Waria Al-Fattah Yogyakarta. This research was conducted with observation, interviews and literature review to reveal the application of prophetic communication used by teachers to transgender students. The findings of this study show that the Pesantren Waria Al-Fattah uses an inclusive prophetic communication approach, which is open to every group, accepts differences and is humanist, there is no coercion in believing in their condition so that transgender community become comfortable in worshiping and learning religion. These findings are important in the development of religious guidance or da'wah for vulnerable and marginalized groups such as this transgender group. Social activists and da'wah can utilize prophetic communication methods to guide the religion of marginalized groups in society through an inclusive and humanist approach.